Wellbeing-responsive community: a growth target for intentional mental health promotion - Raymond, Ivan J.; Burke, Karena J.; Agnew, Kylie J.; Kelly, David M. (Frontiers in Public Health, 2023)
With mental illness remaining a significant burden of disease, there is an ongoing need for community-based health promotion, prevention and responses (or “mental health promotion activities”). The health promotion, community development and positive psychology literature identifies significant heterogeneity in the design and delivery of these activities. This variability spans: (1) individual versus group outcomes, (2) psychological versus sociological determinants of change, (3) promoting wellbeing versus reducing mental health symptoms, and (4) the degree activities are contextualised versus standardised in design and delivery. Mental health promotion activities do not easily accomplish this level of complexity within design and implementation. This has led to the emergence of the complexity-informed health promotion literature, and the need for innovative tools, methods and theories to drive this endeavour. This paper directly responds to this call. It introduces “wellbeing-responsive community”; a vision and outcome hierarchy (or growth target) for intentionally delivered mental health promotion. The construct enables the design and implementation of interventions that intentionally respond to complexity and contextualisation through the drivers of co-creation, intentionality and local empowerment. It represents a community (support team, program, agency, network, school or region) that has the shared language, knowledge, methods and skills to work together in shared intent. In other words, to integrate best-practice science with their local knowledge systems and existing strengths, and intentionally co-create and deliver contextualised wellbeing solutions at both the individual and community level, and spanning the “system” (e.g., whole-of-community) to the “moment” (intentional support and care). Co-creation, as applied through a transdisciplinary lens, is emerging as an evidence-based method to respond to complexity. This paper describes the rationale and evidence underpinning the conceptualisation of wellbeing-responsive community through the integration of three key literatures: (1) positive psychology, (2) ecological or systems approaches and (3) intentional practice (implementation science). A definitional, contextual and applied overview of wellbeing-responsive community is provided, including a hierarchy of outcomes and associated definitions. Its purported application across education, mental health, community service and organisational settings is discussed, including its potential role to make complexity-informed health promotion practical for all knowledge users.